The dynamic of aterosclerosis affection on brachio-cefalic arterys of the high risk patients under the hypolipidemic treatment - V.V. Simerzin; M.A. Kachkovskiy; N.A. Kirichenko; O.A. Rubanenko (Саратовский научно-медицинский журнал, 2010)
Purpose. To study the statin influence on lipid exchange and the degree of the brachiocefalic arterys alteration. Methods. The research included 33 high risk patients. The patients inverstigation included lipid spectrum, blood coagulation indexes, by the means of triplex scanning of the brachiochefalic arterys the thickness of the intima - media complex and the expression of stenosis of carotid, vertebral and subclavian arterys were measured. Results. All the patients were divided into the groups according to the total cholesterol and low density lipoprotein cholesterol levels. Patients were divided into subgroups according to the expression of stenosis. The 1 group of patients received rosuvastating 10 mg, the 2 group - atorvastain 20 mg, 3the 3 group - simvastatin 40 mg. This inverstigation shows that the high risk patients with high levels of total cholesterol and low density lipoproteins have the highest expressiveness of brachiocefalic arterys atherosclerosis affection. Conclusion. The assignment of the statins to these patients is accompanied by the lowering of the levels of total cholesterol and low density lipoproteins and the quantity of arteries affected by the atherosclerosis and also by decreasing of the stenosis expression